2016
DOI: 10.4025/actascianimsci.v38i4.30462
|View full text |Cite
|
Sign up to set email alerts
|

<b>Performance and digestibility in feedlot lambs fed hay based diets

Abstract: This study aimed to evaluate the performance of feedlot lambs fed diets formulated with hay of different genotypes of Cynodon spp. and to compare the dry matter digestibility of diets using different evaluation methods (total fecal collection and chromium oxide). Suffolk crossbred neutered male lambs (n=30), with an average age of 90 days and average body weight of 21.5 kg ± 1.6. Diets were formulated using a standard concentrate and hay of the following genotypes of Cynodon dactylon: Jiggs, Vaquero, Tifton 68… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
0
0
2
Order By: Relevance
“…However, the results are variable because of several factors, including incomplete mixing with ruminal digesta, faster passage through the rumen than fibrous material, possible accumulation in the digestive tract, variations in fecal excretion throughout the day, and analytical difficulties. However, as in the present study, other authors found that CO produced satisfactory results and presented several advantages, including low cost, ease of administration, and ease of analysis (CABRAL et al, 2008;FERREIRA et al, 2009;SAMPAIO et al, 2011;POZZA et al, 2013;OLIVEIRA et al, 2016).…”
Section: Markerssupporting
confidence: 67%
“…However, the results are variable because of several factors, including incomplete mixing with ruminal digesta, faster passage through the rumen than fibrous material, possible accumulation in the digestive tract, variations in fecal excretion throughout the day, and analytical difficulties. However, as in the present study, other authors found that CO produced satisfactory results and presented several advantages, including low cost, ease of administration, and ease of analysis (CABRAL et al, 2008;FERREIRA et al, 2009;SAMPAIO et al, 2011;POZZA et al, 2013;OLIVEIRA et al, 2016).…”
Section: Markerssupporting
confidence: 67%
“…Fonte: Adaptado de Oliveira et al (2016). Aboagye et al (2015) avaliando o desempenho produtivo de ovinos alimentados com feno de alfafa aditivados com: controle, enzima fi brolítica, inoculante microbiano produtor de esterase de ácido ferúlico e enzimas fi brolíticas para controlar a ingestão da dieta, verifi caram que não houve efeito das enzimas sobre o consumo, digestibilidade e desempenho animal.…”
Section: O Processo De Fenação E Suas Etapasunclassified
“…Fonte: Adaptado de Oliveira et al (2016). Aboagye et al (2015) avaliando o desempenho produtivo de ovinos alimentados com feno de alfafa aditivados com: controle, enzima fi brolítica, inoculante microbiano produtor de esterase de ácido ferúlico e enzimas fi brolíticas para controlar a ingestão da dieta, verifi caram que não houve efeito das enzimas sobre o consumo, digestibilidade e desempenho animal.…”
Section: O Processo De Fenação E Suas Etapasunclassified